GREEN HRM PRACTICES AND SUSTAINABILITY IN MANUFACTURING INDUSTRIES - ASAITHAMBI, B.; SUBASHINI, G. S. (International Journal of Psychosocial Rehabilitation, 2020)
Green HRM not only includes consciousness in the direction of environmental affairs, but also stands for the social and economic well-being of both the manufacturing organization and the human resources with a broader view. In recent times, manufacturing organizations aware are about the increasing significance of the incorporation of environmental management techniques and human resource management to adopt green HRM (GHRM) practices. GHRM utilizes the HRM policies to promote the optimal use of resources within business organizations and largely foster the cause of environmental sustainability. Present study aims to determine the relationship between the green human resource factors like green recruitment, green training, management commitment, employee commitment, feedback and review, green rewards and compensation on organization sustainability. Data were collected with the help of self-administered questionnaire from 168 employees in Trichy. Convenience sampling technique was used to gather the data from the respondents. Descriptive facts, correlation, and regression were used to analyze the data using SPSS. The results showed a significant impact of GHRM practices on organizational sustainability, and assert that manufacturing industries in Trichy need to foster the green HRM practices.